Evaluation of β2-microglobulin, IL17, Endostatin levels, and some biochemical variables in patients with Chronic kidney disease in Kirkuk city: Evaluasi kadar β2-mikroglobulin, IL17, Endostatin, dan beberapa variabel biokimia pada pasien penyakit ginjal kronis di kota Kirkuk - Zina Abdulmunem Abdulrazaaq; Nagham Imad Abdul Hameed (Academia Open, 2025)
Chronic kidney disease is the most common disease in developed countries of the world and thus poses a major challenge to public health throughout the world , Method:- Samples were collected randomly from patients hospitalized in Kirkuk General Hospital, in addition to some outpatient medical clinics. 55 samples were collected for patients with chronic kidney disease CKD, whose ages were (40-75) for one year for the period (1/6/2024 to 25/10/2024) Also, 30 blood samples were collected from healthy people (as a control group) .5 ml of blood sample was collected from patients and healthy people and separated using a centrifuge to obtain the serum, after which the level of the studied variables, represented by β2-microglobulin, Interlukin-17- IL-17, Endostatin, and some biochemical variables, which included (Urea, Creatinin, Uric acid, Ferritin )Result:- This study showed a significant rise in the (Β2-MG, Endostatin, IL-17, Urea, Creatinin, Uric acid, and ferritin ) in patients with CKD compared to healthy subjects. Highlights: Chronic kidney disease challenges public health worldwide. Study analyzes β2-MG, IL-17, Endostatin, and biochemical markers in CKD patients. Results show significant biomarker elevation in CKD versus healthy subjects. Keywords: Chronic kidney disease, β2-microglobulin, IL-17, Endostatin